Indigenous family life in Australia: A history of difference and deficit. Issue 3 (1st December 2019) - Dunstan, Laura; Hewitt, Belinda; Nakata, Sana
Abstract: Indigenous family life has been a key target of family and child policies in Australia since colonisation. In this paper, we identify four main policy eras that have shaped the national and state policy frameworks that have impacted Indigenous families: the protectionism, assimilation, self‐determination and neoliberalism eras. Our analysis of these national and state policy frameworks reveals an enduring and negative conceptualisation of Indigenous family life. This conceptualisation continues to position Indigenous families as deficient and dysfunctional compared with a white, Anglo‐Australian family ideal. This contributes to the reproduction of paternalistic policy settings and the racialised hierarchies within them that entrench Indigenous disempowerment and reproduce Indigenous disadvantage. Further, it maintains a deficit paradigm that continues to obfuscate the positive aspects of Indigenous family life that are protective of Indigenous well‐being.